Genotypic and phenotypic analysis in 51 Chinese patients with primary distal renal tubular acidosis. Issue 4 (28th June 2021) - Guo, Wencong; Song, Qijing; Zhang, Ruixiao; Xin, Qing; Liu, Zhiying; Lang, Yanhua; Zhao, Xiangzhong; Shao, Leping
Abstract: The aim of this study was to analyze the genetic variants of 51 Chinese patients with distal renal tubular acidosis (dRTA) and explore the correlation between their genotype and phenotype. Eight variants of SLC4A1, 19 variants of ATP6V0A4, and 16 variants of ATP6V1B1 have been identified, and of which 14 were novel ones. Eleven patients with autosomal dominant dRTA, and four patients with autosomal recessive dRTA were caused by genetic defects in SLC4A1 ; 18 and nine patients with recessive dRTA were resulted by defects in ATP6V0A4 and ATP6V1B1 respectively; no causal gene was identified in seven patients. Mutation frequency of SLC4A1 in Chinese populations was more common than Europeans. The incidence of deafness in ATP6V0A4 and ATP6V1B1 groups was 16.7% and 54.5%, respectively. The frequency of CKD in adults, children and infants was 100%, 51%, and 3%, separately. Our study will further expand the mutation spectrum of primary dRTA and provide valuable references to genetic counseling of Chinese populations. Abstract :